An account of the genus Cistanche (Orobanchaceae) in Iraq and taxonomic considerations in the Middle East - Majed Aldughayman; Chris J. Thorogood; Abdulridha A. A. Al-Mayah; Julie A. Hawkins (PhytoKeys, 2024)
Species limits in the genus Cistanche are poorly understood, despite the plants’ long history of use in traditional herbal medicine and food across their range. Here we present a taxonomic account for the genus Cistanche in Iraq, where several taxa have been reported, most of them doubtfully. Using herbarium specimens, images of living material, and taxonomic literature, we found evidence of only one species occurring with certainty in Iraq: Cistanche tubulosa. We found no evidence for the occurrence of other Cistanche species in Iraq, including a putative new entity reported for the region. Our work highlights inconsistencies in the literature, and underscores the importance of examining multiple stable characters for delimiting species in the genus Cistanche.